TEKNIK PENGELOLAAN ZAKAT PROFESI (ZISWAF: Jurnal Zakat dan Wakaf, 2015)
Zakat means blessing, grow, clean and good. the expected tithe heart, his soul and his wealth will be clean. Law No. 38 of 1999 on themanagement of zakat, it regulates the implementation, monitoring, collectionand dissemination and utilization of zakat. This law does not restrict the textexplicitly only as zakat of gold and silver, trade, agriculture, mining, rikazbut also charity and service revenue. In accordance with the MUI No. 3of 2003 which requires the zakat income or profession. , The legal basis forsuch charity; (Q.S Al-Baqarah: 43). Compulsory zakat: independence, Islam,puberty, understanding, property is property that must Zakat, has reachednishab property, property owned, have passed one year, no debt, exceedingstaples, property obtained by good and lawful and grow. While the legalconditions zakat; muzakki intentions and the transfer of ownership of muzakkito mustahiq. Profession means jobs. Various professions kasb al-charity,which works well for someone else to make the government, companies, andindividuals to obtain wage, granted, hand, brain or both. Incomes in the formof wages, salary or honorarium, such as civil servants, private employeesand staff of the company, and Mihan al-hurray, the work done on their ownwithout depending on others, thanks to the dexterity of the hand or brain, hisincome is income professionals, such as doctors, engineers, lawyers, artists,and others. Zakat Profession zakah is imposed on the income of each job orprofessional expertise, whether it is done alone or carried out jointly with thepeople / institutions that can generate revenue (money) that meet nishab (theminimum limit of treasures to be tithe). Socialization from the governmentand related clerical profession zakat management is absolutely necessaryand is a key and essential factor in realizing the implementation of zakatprofession. To raise awareness of the tithe among civil servants and staff of thecompany to do: (a) provide insight (know-how) are properly and adequatelyabout zakat, infaq and sadaqah, both in terms of epistemology, terminology,and kedudukanya in Islam, (b) benefits (benefit) and lavatory (need) of zakat,sadaqah infaq and, especially for the culprit or the mustahiq zakat (c) there isan example of a leader. Technical charity fundraiser the most simple and easyfor administrators is to cut the salaries of the employees immediately uponpayment each month, by 2.5%, it is intended to facilitate the implementationof pengumpulanya.